Approximation of modulus, periods and values of Jacobi elliptic functions - Barabash, G.M.; Kholyavka, Ya.M. (Carpathian Mathematical Publications, 2014)
Let sn_i (z), i=1,2, be algebraically independent Jacobi elliptic functions. We obtain an estimation of a simultaneous approximation of modulus of these functions, their periods, arbitrary number α and the values of each of these functions at the periods of the other function and at the point α.